2020
DOI: 10.1109/access.2020.2981252
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Achieve Single-Polarization Guidance in Hollow-Core Negative- Curvature Fibers

Abstract: We propose a new method to achieve single-polarization guidance in a hollow-core negativecurvature fiber. Simulation results show that coating a layer of high-index material with a suitable thickness on the inner surface of one vertical cladding tube in a hollow-core negative-curvature fiber can effectively suppress y-polarized fundamental mode. Silicon is chosen as the high-index material in this paper. In the five-nested-tube silicon-coated negative-curvature fiber, the single-polarization region is located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Only a small number of theoretical and experimental studies have been found so far to obtainHi-Bi and PM features on HC-ARFs since researchers are now focusing on enhancingthe birefringence of HC-ARFs [11,[20][21][22][23][24][25][26][27][28][29]. For instance, despite having numerous stacked layers and four cladding tubes with a tiny core diameter of 14 µm, Mousavi et al's rst HiBi HC-ARF demonstration generated a Hi-Bi of 1.5×10 − 4 at 1550 nm with a loss of 0.043 dB/m [11,20].However, the composition consisted of four external tubing layers incorporating numerous nested resonator layers, with a relatively compact core size of 14 µm.In a numerical investigation of a six tube AR-HCF with two nested elements, a low birefringence of 1.3×10 − 5 at 1550 nm with a CL of 0.02 dB/m was obtained [22].Additionally, the six-tube bi-thickness HC-ARF developed by Yerolatsitis and colleagues [24]had a lower birefringence of 2.5×10 − 5 and a higher loss of 0.46 dB/m at 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of theoretical and experimental studies have been found so far to obtainHi-Bi and PM features on HC-ARFs since researchers are now focusing on enhancingthe birefringence of HC-ARFs [11,[20][21][22][23][24][25][26][27][28][29]. For instance, despite having numerous stacked layers and four cladding tubes with a tiny core diameter of 14 µm, Mousavi et al's rst HiBi HC-ARF demonstration generated a Hi-Bi of 1.5×10 − 4 at 1550 nm with a loss of 0.043 dB/m [11,20].However, the composition consisted of four external tubing layers incorporating numerous nested resonator layers, with a relatively compact core size of 14 µm.In a numerical investigation of a six tube AR-HCF with two nested elements, a low birefringence of 1.3×10 − 5 at 1550 nm with a CL of 0.02 dB/m was obtained [22].Additionally, the six-tube bi-thickness HC-ARF developed by Yerolatsitis and colleagues [24]had a lower birefringence of 2.5×10 − 5 and a higher loss of 0.46 dB/m at 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few high-bireringence and single-polarization HC-ARF designs have been proposed in the near-IR regime mostly at 1550 nm or 1064 nm with different cladding arrangements and number of layers in the cladding structure [18]- [21]. High-birefringence and singlepolarization were achieved either by using multiple nested resonators [18], [21] or high index materials in the cladding [19], [20]. Most recently, a four-fold [21] and six-fold [22] symmetry bi-thickness HC-ARF were experimentally reported with outstanding optical performances.…”
Section: Introductionmentioning
confidence: 99%
“…have the potential to be used for long-distance communication. In addition, ARFs can also be used in other fields, such as polarization maintainence [8][9][10], biochemical sensing [11], and thermal imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the coupling between the high-order core modes and the cladding mode with high loss, the operation of single mode can be realized in ARFs [14,15]. In addition, several single linearly polarized single-mode ARFs have been reported that introduce linear birefringence, which can operate in the near-infrared, mid-infrared and terahertz regions [8][9][10]. Similarly, to implement the operation of single-mode single-circular polarization (SMSCP), ARFs need to have circular -birefringence.…”
Section: Introductionmentioning
confidence: 99%